Endovascular thrombectomy for acute ischemic stroke in patients with cancer: a propensity-matched analysis. (8th December 2021) - Joshi, Krishna C; Grewal, Parneet; Beer-Furlan, André; Vargas, Alejandro; Osteraas, Nicholas; Dafer, Rima; Chen, Michael
Abstract : Background: There is a paucity of data and a belief that endovascular thrombectomy (EVT) has low efficacy for acute ischemic stroke (AIS) in patients with cancer. We aimed to critically compare the clinical outcomes of EVT for AIS in patients with and without cancer. Methods: Records of all patients undergoing EVT for AIS between January 2015 and 2020 were screened for cancer at the time of EVT. Active cancer was defined as patients who were diagnosed with cancer and were undergoing or refused treatment for that cancer. Baseline modified Rankin Scale (mRS), age and sex were used in a 1:5 propensity score matching ratio. After matching we evaluated for any change in the National Institutes of Health Stroke Scale (NIHSS) from baseline to discharge, hemorrhagic transformation (HT), and 90-day mRS and mortality. Results: There were 19 patients with cancer and 95 matched controls. The mean±SD age was 70.89±11.16 years, and 17 (89.47%) were female. The baseline NIHSS was 22± 7.5 and baseline mRS was 1 (IQR 1). There was no significant difference in change in baseline to discharge NIHSS, 90-day mRS or mortality; 90-day mRS 0–2 was 45.2% in the non-cancer group versus 46.7% in cancer group (p=0.54). HT was significantly higher in patients with cancer (57.89% vs 6.49%, p<0.001). Conclusions: In propensity matched analysis of patients undergoing EVT for AIS with and without cancer, 90-day functional outcomes and mortality were similar. However, there was a significantly higher rate of HT in cancer patients.